Adjustment of a rapid method for quantification of Fusarium spp. spore suspensions in plant pathology = Ajuste de un método rápido para la cuantificación de suspensiones de esporas de Fusarium spp. en fitopatología - Caligiore Gei, Pablo Fernando (2015)
The use of a Neubauer chamber is a broadly employed method when cell suspensions need to be quantified. However, this technique may take a long time and needs trained personnel. Spectrophotometry has proved to be a rapid, simple and accurate method to estimate the concentration of spore suspensions of isolates of the genus Fusarium. In this work we present a linear formula to relate absorbance measurements at 530 nm with the number of microconidia/ml in a suspension.